Evidence about properties of the extract of Stryphnodendron adstringens (Mart.) Coville (Barbatimão) for clinical practice (Research, Society and Development, 2021)
The aim of this study was to highlight the evidence about the properties of the extract of Stryphnodendron adstringens (Mart.) Coville (Barbatimão) and your application to human health. For this purpose, the CAPES Periodic Portal, Scielo, ScienceDirect, PubMed and Scopus databases were searched regarding the period from 2002 to 2019. This is a review of all studies published since 2002 on about properties of the extract of Stryphnodendron adstringens (Mart.) Coville (Barbatimão). Although in vitro and in vivo studies have shown that anticancer, antimicrobial, antiviral, fungical, anti-inflammatory and healing properties. In addition, particular clinical conditions also had improvement of the clinical condition in view of the use of Barbatimão including decreases in serum glucose, arthritis and Alzheimer's disease.